A construção do ethos no Tribunal do Júri: um olhar retórico-discursivo para o Caso Kiss - Herold, Gabrieli Dorigon (2025)
This research investigates the construction of the defendant Luciano Bonilha Leão’s ethos during his testimony in the Jury Court of the Kiss Case, held in December 2021. The Jury Court is regulated by Brazilian law as mandatory in cases of crimes against life. It is a highly standardized genre, with perpetuated ritualistic acts and well-determined social roles. It is considered, therefore, that to persuade the jurors of their innocence, the defendant and defense lawyer use numerous argumentative strategies that corroborate the construction of an image that guarantees the desired freedom. Thus, the ethos, mobilized from the targeted argumentative of the discourse (Amossy, 2020), assumes the role of negotiating certain senses with the audience from the speaker’s objective, constituting one of the most important forms of persuasion (Aristotle, 2005). To achieve the general objective of investigating the construction of the ethos during the defendant’s testimony in the Jury, we determined as specific objectives, 1) to understand the linguistic and institutional dimension of the argumentation and ethos in the testimony of the defendant Luciano Bonilha Leão, highlighting the strategies that the speaker mobilizes to (re)build his image during the testimony; 2) to analyze the corpus based on some aspects of the linguistic dimension (lexical choices and designations employed in materiality), paralinguistic (intonation, pauses, emphases, posture, gestures, clothing) and contextual; and 3) relate the language with the institutional dimension of discourse (field, social roles, gender of discourse, doxa and previous ethos). We are based on the intersection between Rhetoric and Discourse Analysis proposed by Amossy (2016; 2020), assuming the subject as an agent of his choices and, at the same time, restricted by the social and generic framework. The results of the research reveal that the ethos of the defendant is built from three main images: humility, innocence and virtue, designed in response to the previous ethos of greedy, guilty and murderer, designed mainly by the instance of accusation. It is also noticed that the speaker projects an image on himself as he builds a certain image on the other. With this, the ethos reveals one of the most powerful forms of persuasion in the criminal-legal sphere of the Jury Court, whose functioning takes place by a clash of images built through language and intentionally directed.